Upper extremity injuries associated with strength training - Haupt, H. A. (Clinics in Sports Medicine, 2001)
Most injuries sustained during strength training are mild strains that resolve with appropriate rest. More severe injuries include traumatic shoulder dislocations, tendon ruptures of the pectoralis major, biceps, and triceps; stress fractures of the distal clavicle, humerus, radius, and ulna; traumatic fractures of the distal radius and ulna in adolescent weightlifters; and compressive and stretch neuropathies. These more severe injuries are usually the result of improperly performing a strength training exercise. Educating athletes regarding proper strength-training techniques serves to reverse established injury patterns and to prevent these injuries in the first place. Recognizing the association of anabolic steroid use to several of the injury patterns further reinforces the need for medical specialists to counsel athletes against their use. With the increasing use of supplements such as creatine, the incidence and nature of strength-training injuries may change further. Greater emphasis on the competitive performance of younger athletes undoubtedly will generate enthusiasm for strength training at earlier ages in both sexes. The importance of proper supervision of these young athletes by knowledgeable persons will increase. As the popularity of strength training grows, there will be ample opportunity to continue to catalog the injury patterns associated with this activity.